THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY AND GOOD CORPORATE GOVERNANCE ON FINANCIAL PERFORMANCE IN MANUFACTURING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Dompak Pasaribu; Ivo Maelina Silitonga; Lidya Paskalina Pasaribu (PT. Radja Intercontinental Publishing, 2023)
This research aims to examine the influence of Corporate Social Responsibility and Good Corporate Governance as proxied by independent commissioners, audit committees, institutional ownership, managerial ownership on financial performance as measured by Return On Assets. The number of samples used in this research were 20 manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2017-2021 period. This research uses secondary data. The sampling technique used was purposive sampling. Data were analyzed using multiple linear regression models. This research produces findings that Corporate Social Responsibility, the audit committee has a positive but not significant effect, independent commissioners have a positive and significant effect, and institutional ownership, managerial ownership has a negative and not significant effect on financial performance, as well as Corporate Social Responsibility, independent commissioners, audit committees, Institutional ownership and managerial ownership together influence financial performance.